Selling online 2.0 : migrating from eBay to Amazon, Craigslist, and your own e-commerce website - Miller, Michael, 1958- (Que, 2009)
REMEMBER WHEN eBay USED TO BE A GREAT PLACE FOR SMALL SELLERS TO BECOME BIG SELLERS? Unfortunately, recent changes at eBay have made online auctions less reliable and profitable. So where can you sell when you can't sell on eBay? Online auctions are the past; fixed-price selling is the future. It's time to move beyond eBay and first-generation online selling and start Selling Online 2.0. Second generation online selling means migrating from eBay to other online marketplaces, including craigslist, Amazon, and your own e-commerce website. You'll need to make some new plans, learn some new skills, and change some of the things you do--but you'll find that there's more money to be made on your own than relying on traditional eBay online auction sales. Put together a plan to maintain your sales level and profitability--to counteract eBay's changes Discover how to shift from auction sales to fixed-priced listings on the eBay marketplace Find out if running an eBay Store or selling on Half.com makes sense for your business Learn out how to sell locally on craigslist and other online classifieds sites Discover how to sell fixed-price merchandise on the Amazon marketplace Find out how to launch your own e-commerce website--and promote your online store Learn how to sell products across multiple channels--and manage multichannel conflicts Introduction 1 What's in This Book 2 Who Can Use This Book 3 How to Use This Book 3 There's More Online ... 4 Making the Move 4 I BEYOND ONLINE AUCTIONS: CREATING A SUCCESSFUL ONLINE BUSINESS 5 1 The Problem with Online Auctions 7 What eBay Used to Be Like ... 7 Why Is eBay Abandoning Smaller Sellers? 10 Changes Are Afoot--and You Probably Won't Like Them 12 Emphasizing Fixed-Price Sales over Auction Sales 12 Changes to the Fee Structure 12 Changes to the Payment System 14 Changes to the Feedback System 15 Changes to Search Results 15 eBay's Deal with Buy.com 16 How Do eBay's Changes Affect You? 16 2 Planning for Selling Success 19 Planning for Life Beyond eBay Auctions 19 Asking--and Answering--Key Questions 20 What Type of Merchandise Do You Want to Sell? 20 How Much Money Do You Want to Make? 21 How Do You Intend to Manage Your Business? 23 Where Do You Want to Sell? 25 Conceiving a Business Plan 26 Understanding the Components of a Useful Business Plan 28 Mission 29 Opportunity 30 Strategy 30 Organization ...